THE ROLE OF SATISFACTION IN MEDIATING THE INFLUENCE OF PRODUCT QUALITY ON CUSTOMER LOYALTY IN INDOMILK PACKAGED MILK PRODUCTS IN DENPASAR - Made Aditya Saputra; Tjokorda Gde Raka Sukawati (Adisam Publisher, 2024)
Business in Indonesia is incredibly competitive, thus every company works hard to augment their customer base while simultaneously satisfying current customers and finding new ones. Indomilk, a brand of dairy products, is experiencing a phenomenon whereby customer loyalty is being impacted by falling sales volume and the Top Brand Index. Indomilk packaged milk products in Denpasar are the focus of this investigation, which aims to determine the role of consumer pleasure in mediating the relationship between product quality and brand loyalty. The sample for the investigation consisted of 110 participants chosen using a combination of non-probability and purposive selection methods. Information is analysed using Path Analysis in conjunction with the Sobel Test and the Variance Accounted for (VAF) Test. Product quality has a good and substantial effect on customer satisfaction, which has a positive and substantial effect on customer loyalty, in light of the outcomes of the study. Furthermore, product quality indirectly influences customer loyalty via customer satisfaction. In light of the investigation, Indomilk should improve the quality of its raw materials, augment the amount of attention-grabbing colours and patterns used in product packaging, and maintain a constant level of high-quality items.